Trump, Russia, and China: The First 100 Days - Share, M. (Meždunarodnaâ analitika, 2017)
On April 30 the United States and the World marked the 100th day in office of Donald Trump as President of the United States. The first 100 days are considered as a key indicator of the fortunes for a new President’s program. This article briefly reviews the 2016 campaign and election, the 11 week transition period, his first 100 days, a brief examination of both American-Russian relations and Sino-American relations, and lastly, what the future bodes for each under a Trump Presidency. The 100 Day period has been chaotic, shifting, and at times incoherent. He has made 180 degree shifts toward many major issues, including Russia and China, which has only confused numerous world leaders, including Presidents Putin and Xi. There has been a definite disconnection between what Trump says about Russia, and what his advisors and cabinet officials say. So far Trump has conducted a highly personalized and transactional foreign policy. All is up for negotiation at this a huge turning point in American foreign policy, the greatest one since 1945. Given all the world’s instabilities today, a rapprochement between the United States and Russia is a truly worthwhile objective, and should be strongly pursued.